2000
DOI: 10.1111/j.1365-2621.2000.tb16067.x
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Diffusion and Desorption Isotherms for Banana

Abstract: The desorption isotherms for whole peeled banana, convection dried in warm air, have been measured and fitted by the Modified-Oswin and Modified-Chung-Pfost equations. The equations agreed with the water activity observed in commercial sun-dried banana packs from Thailand. The convective drying curves for peeled banana were determined and fitted by the Newton (exponential) and Diffusion models. The Newton model was found more effective, probably due to a surface resistance that develops during drying. The dryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 16 publications
5
39
0
Order By: Relevance
“…Therefore, it could be concluded that a single model is not sufficient to describe the adsorption behaviour in terms of both M = f(rh, T) and rh = f(M, T). These types of fitting results were also reported by Sun and Woods (1994) and Phoungchandang and Woods (2000).…”
Section: Fitting Of Sorption Equations To Experimental Datasupporting
confidence: 81%
“…Therefore, it could be concluded that a single model is not sufficient to describe the adsorption behaviour in terms of both M = f(rh, T) and rh = f(M, T). These types of fitting results were also reported by Sun and Woods (1994) and Phoungchandang and Woods (2000).…”
Section: Fitting Of Sorption Equations To Experimental Datasupporting
confidence: 81%
“…The Arrhenius law is often used to describe the relationship (Madamba et al, 1996;Mazza & Le Maguer, 1980;Mulet et al, 1989;Newman, Price, & Woolf, 1996;Phoungchandang & Woods, 2000a;Yusheng & Poulsen, 1988), sometimes expressed in terms of a finite reference temperature, T ref :…”
Section: Dependence Of Diffusivity On Temperature and Water Contentmentioning
confidence: 99%
“…Interestingly, the "Zero model" used the simplified form of moisture ratio as X/X 0 instead of (X-X e )/(X 0 -X e ) by taking the equilibrium moisture content (X e )00 in Eq. (13) (Phoungchandang and Woods 2000). The R 2 for the model were rather high (more than 0.957) with low SEE (lower than 0.081 % d.b.…”
Section: Modeling Of Drying Kinetics Of C Asiatica Leavesmentioning
confidence: 89%
“…Fresh and blanched C. asiatica leaves were placed on a preweighted drying tray in order to proceed to the thin-layer drying process using a tray dryer (Armfield Limited, Hampshire, England) at 50°C to obtain seven different levels of moisture content (Phoungchandang and Woods 2000). The dried leaves of 0.5 g were measured for equilibrium relative humidity at 20, 35 and 50°C, respectively, by using Aqualab (Series 3TE, Devices, America) that is specially designed for temperature -controlled dew point of water activity or relative humidity at equilibrium state with an accuracy of 0.01 %.…”
Section: Desorption Isothermsmentioning
confidence: 99%